Evaluation of gastrointestinal complications in Egyptian patients after autologous stem cell transplantation using melphalan-based regimens - Mona Mahrous Abdelaty; Fatma Al-Hosiny; Raghda Gabr Mashaal (SpringerOpen, 2023)
Abstract Background Autologous stem cell transplantation (ASCT) is a curative treatment for patients with hematological malignancies. Melphalan either alone or in combination with other chemotherapeutic agents is a widely used pre-transplant conditioning regimen with known gastrointestinal (GI) complications. We retrospectively evaluate the incidence and severity of GI toxicities, the possible risk factors, and their impact on transplant outcomes in 47 patients who received ASCT using melphalan-based conditioning. Results Median age was 50 years. Among our patients, 48.9% received melphalan at 200 mg/m2. Mucositis was developed in 93.6% of patients, nausea in 87.2% and grade 2 vomiting in 36.2% of patients. Grade 3 diarrhea was detected in 42.6%. Severe GI toxicities were associated with significantly delayed engraftment, longer hospital stay, and increased transfusion requirements but overall survival (OS) and transplant-related mortality (TRM) were not affected by the severity of GI symptoms. Conclusion Despite using prophylactic and supportive care, some patients developed severe GI complications following different doses of melphalan with a negative effect on some transplant outcomes. Melphalan dose or disease type was not identified as a risk factor for severe GI toxicity. Additional larger prospective studies with higher doses, different formulations, and better prophylactic measures are warranted to evaluate potential risk factors and their impact on GI toxicities.